2008
DOI: 10.4049/jimmunol.180.7.4507
|View full text |Cite
|
Sign up to set email alerts
|

Brief Antigenic Stimulation Generates Effector CD8 T Cells with Low Cytotoxic Activity and High IL-2 Production

Abstract: It is currently believed that a brief antigenic stimulation is sufficient to induce CD8 T cells to complete their differentiation program, become effector T cells, and subsequently generate memory. Because this concept was derived from studies in which only a single effector function was analyzed (either IFN-γ production or target cell lysis), we wondered whether monitoring for multiple effector functions might reveal novel characteristics of effector CD8 T cells elicited by brief or prolonged Ag exposure. Usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
(40 reference statements)
1
4
0
Order By: Relevance
“…However, it is known that virus-specific CD8 T cells down-regulate CD27 during latent MCMV infection (24, 66), and we found that the expression of this surface marker was further reduced in IL-10 −/− mice. One possible functional consequence of CD27 down-regulation in this study was reduced IL-2 production in response to antigen stimulation; this is consistent with previous studies linking cellular differentiation to the loss of IL-2 expression (67, 68) and suggests a role for CD4 T cell help in the maintenance of polyfunctional memory CD8 T cells (69). Furthermore, highly differentiated CD8 T cells express high levels of granzyme and perforin (66, 70, 71) thereby suggesting that these cells are cytotoxic.…”
Section: Discussionsupporting
confidence: 92%
“…However, it is known that virus-specific CD8 T cells down-regulate CD27 during latent MCMV infection (24, 66), and we found that the expression of this surface marker was further reduced in IL-10 −/− mice. One possible functional consequence of CD27 down-regulation in this study was reduced IL-2 production in response to antigen stimulation; this is consistent with previous studies linking cellular differentiation to the loss of IL-2 expression (67, 68) and suggests a role for CD4 T cell help in the maintenance of polyfunctional memory CD8 T cells (69). Furthermore, highly differentiated CD8 T cells express high levels of granzyme and perforin (66, 70, 71) thereby suggesting that these cells are cytotoxic.…”
Section: Discussionsupporting
confidence: 92%
“…43,44 Studies evaluating the influence of antigen signaling duration rather than DC maturation state have demonstrated that CD8 ϩ T cells receiving a brief antigenic stimulus similarly acquire a central memory phenotype and produce significantly more IL2 compared with T cells receiving prolonged antigen stimulation, which developed cytotoxic activity and a reduced ability to produce IL2. 45 This reduced differentiation of primed T cells is in agreement with a progressive differentiation model in which differences in costimulation or cytokines provided in the local milieu result in varying signal strength provided to individual naive T cells, promoting a response composed of a spectrum of T cells that have acquired different amounts of effector functions and differentiation. 46 Our results suggest that the enhanced number of CD8 ϩ T cells acquiring limited effector functions and retaining CD28 generated by priming with LPS/R848-matured DCs may result from T cells primed in the presence of the incompletely mature subpopulations of DCs that provide a reduced signal for expansion, resulting in a reduced differentiation of T cells.…”
Section: Tlr-enhanced Generation Of Cd28mentioning
confidence: 52%
“…Umbilical cord cells are known to produce high amounts of IL‐2, in both CD4+ and CD8+ T cell subsets (21), and constitutive production in CD4+ T cells may decrease over time as culture substrate is depleted. Brief antigen stimulation also results in increased IL‐2 production in CD8+ T cells without concurrent increase in cytotoxic activity (22). It is possible that introduction of antigen through delivery, sample collection or processing could provide enough stimulus to increase background IL‐2 production of CD8+ T cells in a the given period of time; this effect may be more evident in umbilical cord samples which produce high amounts of IL‐2 at baseline.…”
Section: Discussionmentioning
confidence: 99%